2017
DOI: 10.1038/ncomms15934
|View full text |Cite
|
Sign up to set email alerts
|

GroEL actively stimulates folding of the endogenous substrate protein PepQ

Abstract: Many essential proteins cannot fold without help from chaperonins, like the GroELS system of Escherichia coli. How chaperonins accelerate protein folding remains controversial. Here we test key predictions of both passive and active models of GroELS-stimulated folding, using the endogenous E. coli metalloprotease PepQ. While GroELS increases the folding rate of PepQ by over 15-fold, we demonstrate that slow spontaneous folding of PepQ is not caused by aggregation. Fluorescence measurements suggest that, when f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 81 publications
(239 reference statements)
3
52
0
Order By: Relevance
“…Several proteins utilizing this system have been shown to populate dynamic folding intermediates that convert only slowly to the native state due to a long search time for the formation of native contacts [57][58][59] . Their encapsulation in the folding cage formed by GroEL and GroES results in a rate enhancement of folding by one to two orders of magnitude 57,58,60,61 , which has been attributed to an effect of entropic confinement [56][57][58] . In contrast, KJE-mediated binding and release cycles fail to accelerate the folding of these proteins but rather slow their folding kinetics 19,58,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins utilizing this system have been shown to populate dynamic folding intermediates that convert only slowly to the native state due to a long search time for the formation of native contacts [57][58][59] . Their encapsulation in the folding cage formed by GroEL and GroES results in a rate enhancement of folding by one to two orders of magnitude 57,58,60,61 , which has been attributed to an effect of entropic confinement [56][57][58] . In contrast, KJE-mediated binding and release cycles fail to accelerate the folding of these proteins but rather slow their folding kinetics 19,58,60 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that by encapsulating single protein molecules in its central cavity, GroEL/ES allows folding to proceed unimpaired by aggregation. Work over the past two decades has moved our understanding beyond this fundamental principle and demonstrated that the chaperonin nanocage represents a privileged folding environment in which formation of kinetically trapped intermediates that would otherwise slow or halt spontaneous folding is avoided [55,60–62]. As a result, GroEL/ES provides kinetic assistance to the folding process and accelerates the folding of various proteins ~ 20‐ to 100‐fold above their spontaneous folding rate.…”
Section: Catalysis Of Folding By the Groel/es Chaperoninmentioning
confidence: 99%
“…As a result, GroEL/ES provides kinetic assistance to the folding process and accelerates the folding of various proteins ~ 20‐ to 100‐fold above their spontaneous folding rate. These include destabilized variants of maltose‐binding protein (MBP) [59,60,63–65], Rhodospirillum rubrum Rubisco [66,67], bacterial proteins with topological knots [68], the E. coli prolidase enzyme PepQ [62], and several E. coli proteins with a (βα)8 TIM‐barrel fold [55,61]. In all cases, the slower rate of spontaneous folding was not due to transient aggregation, implying that the chaperonin altered the folding energy landscape for these substrates.…”
Section: Catalysis Of Folding By the Groel/es Chaperoninmentioning
confidence: 99%
“…It is not uncommon to observe both small- and large-scale symmetry breakage of ordered oligomers induced by protein-protein interactions. For example, structures of protein substrate and nucleotide interactions with GroEL, a tetradecameric ring chaperonin protein, show very discernable asymmetric adjustments due to protein substrate interactions [ 36 , 37 ], as well as ATP binding and hydrolysis [ 38 ]. A more dramatic demonstration for ligand-induced distortion of symmetry is observed for the ATP bound vs. ADP bound ATPase unfolding machinery of the valosin-containing protein-like ATPase (VAT) recently resolved by cryo-EM [ 39 ].…”
Section: Discussionmentioning
confidence: 99%